Dealing with Dad [videorecording (DVD)] - Huang, Tom; Maki, Ally, 1986-; Szeto, Hayden, 1985-; Kim, Peter S.; Lee, Dana (Actor) (Indie Rights Movies, 2024)
Margaret Chang reluctantly returns to her hometown along with her hapless brothers to deal with the sudden depression of their complete-jerk father, whom everyone happens to hate. In fact, he's actually more pleasant being depressed, so the siblings wonder if it's worth struggling to get him better. In the meantime, their forced time together allows them to reconnect as a family, reminisce about the bad times with Dad and maybe even help each other out in the process in this multi-award-winning comedic drama feature film.